Perception of public corruption in Kenya - DOUGLAS KIMEMIA (African Journal of Governance and Development, 2013)
Corruption decreases government efficiency and effectiveness, and influences the way citizens perceive the overall quality of the government. The main focus of this paper is to examine why perceptions of public corruption did not change during the Kibaki administration. This administration was in power for 10 years (2003-2013), and invested significant resources in setting up a legislative framework and an anti-corruption agency. Yet, according to the analysis of the Global Corruption Barometer (GCB) reports from 2003 to 2012, there was no change in the public’s perception of corruption and of government effort against corruption. Despite anticorruption agency efforts, optimism dropped, while pessimism increased. To bridge this gap requires political commitment, which is demonstrated by charging all corrupt public officials and recovering any public funds and assets that have been stolen.